348 A workplace intervention targeting obesity and diabetes in Latino farmworkers. (11th October 2013) - Schenker, M B S; Scott,; Andrews,; Mitchell,
Abstract : Objectives: To demonstrate the importance of a workplace modality in targeting a difficult to access community of Latino farm workers with the goal of preventing and reducing morbidities associated with diabetes and obesity. Methods: 254 Latino farm workers were recruited in a California occupational setting. Enrollees were randomly placed in the intervention or control arms (2:1 ratio). All were interviewed at baseline, anthropometric measures and fasting blood glucose were assessed. The intervention consisted of weekly participatory education classes, demonstrations and exercise over a 10-week period. Final evaluation repeated the baseline assessments. 178 farm workers (70%) completed the follow up screening. Results: 112 individuals, 27 males and 85 females completed the intervention for 6 weeks or more, resulting in a 63% completion rate. Amongst the female intervention cohort, all anthropometric mean measures improved. BMI decreased by 0.39 units (95%CI -0.64 to -0.15), weight decreased compared to baseline by 1.47 lb (-2.77 to -0.17), waist decreased by 1.09 cm (-1.93 to -0.26) compared to baseline. Men showed similar directional effects, yet not statistically significant, perhaps limited by smaller enrollment numbers. Significant improvement in days of exercise per week improved in males and females who received the intervention compared with controls. Comparison of intervention vs. control cohorts will also be presented. Conclusion: Latino farm workers are difficult to access through traditional health interventions and suffer disproportionate morbidities from increased rates of obesity and diabetes. Integrating health interventions through a culturally sensitive workplace program allows for increased access to this community and yields significant gains in health.